TANTANGAN DAN PELUANG IMPLEMENTASI PENDIDIKAN INKLUSI: STUDI KASUS DI SEKOLAH DASAR NEGERI 016 SUNGAI KUNJANG - Salim, Nur Agus; Arifin, Nurdin; Wulandari, Asih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to identify challenges and analyze opportunities in the implementation of inclusive education at SD Negeri 016 Sungai Kunjang. Using a qualitative approach with a case study design, the research involved 11 informants consisting of the principal, six classroom teachers, two Special Education Teachers (GPK), and two parents of Students with Special Needs (PDBK). Data were collected through in-depth interviews, observations, and documentation, then analyzed using the Miles and Huberman model. The research identified nine main findings: understanding of inclusion is not uniform, curriculum is adjusted but limited, inadequate number of GPK (2 GPK for 54 PDBK), classroom teachers experience dual burdens, minimal facilities and infrastructure, operational funds are unavailable, collaboration is beginning to form but not optimal, teacher training is rarely conducted, and the attitude of regular students is quite positive. This research concludes that inclusive education can be optimized through strengthening support systems, enhancing teacher capacity, providing special budgets, and structured collaboration between schools, parents, and government.